On the properties and radiative effects of small convective clouds during the eastern Mediterranean summer - Eitan Hirsch; Ilan Koren; Orit Altaratz; Eyal Agassi (Environmental Research Letters, 2015)
A ground-based field campaign was conducted over the summer of 2011 in Israel to measure the properties of small warm clouds. The horizontal size distribution for cloud sizes of 50–3000 m is presented, with a special focus on the properties of the smallest clouds (liquid water path <10 g m ^−2 , cloud thickness < ∼50 m) and their estimated radiative effect. We show that these small clouds dominate the cloud radiative properties during the summer over the studied region. The average daily cloud cover of the small cloud subset throughout the field campaign was 81 ± 21% (corresponding to 30 ± 14.3% of the total measured time), and they contributed 83 ± 19.4% of the clouds' reflectance. Their average daily radiative effect was estimated at −3.6 ± 2.1 W m ^−2 .